Pengembangan Pesantren Modern Melalui Digitalisasi Sistem Pendidikan Islam Berbasis Santrilink - Sunaji, Sunaji (Jaanur Elbarik Indonesia, 2025)
This study aims to explore and develop a digital-based Islamic education system through the implementation of the SantriLink application in the Sunan Drajat Islamic boarding school environment. This study uses a qualitative approach using observation, interview, and document analysis methods at the Sunan Drajat Islamic Boarding School. The results of the study indicate that the implementation of SantriLink has a positive impact on the effectiveness of Islamic boarding school management, transparency of student administration, and increased parental participation in the education process. In addition, the digital system supports the formation of a more structured and measurable learning culture. This study recommends the wider implementation of SantriLink in other Islamic boarding schools as part of the national strategy for modernizing Islamic education